Patterns of siderophore production and utilization at Station ALOHA from the surface to mesopelagic waters - Randelle M. Bundy; Lauren E. Manck; Daniel J. Repeta; Matthew J. Church; Nicholas J. Hawco; Rene M. Boiteau; Jiwoon Park; Edward F. DeLong; Mak A. Saito (Limnology and Oceanography, 2025)
The North Pacific subtropical gyre is a globally important contributor to carbon uptake despite being a persistently oligotrophic ecosystem. Supply of the micronutrient iron to the upper ocean varies seasonally to episodically, and when coupled with rapid biological consumption, results in low iron concentrations. In this study, we examined changes in iron uptake rates, along with siderophore concentrations and biosynthesis potential at Station ALOHA across time (2013–2016) and depth (surface to 500 m) to observe changes in iron acquisition and internal cycling by the microbial community. The genetic potential for siderophore biosynthesis was widespread throughout the upper water column, and biosynthetic gene clusters peaked in spring and summer along with siderophore concentrations, suggesting changes in nutrient delivery, primary production, and carbon export seasonally impact iron acquisition. Dissolved iron turnover times, calculated from iron‐amended experiments in surface (15 m) and mesopelagic (300 m) waters, ranged from 9 to 252 d. The shortest average turnover times at both depths were associated with inorganic iron additions (14 9 d) and the longest with iron bound to strong siderophores (148 225 d). Uptake rates of siderophore‐bound iron were faster in mesopelagic waters than in the surface, leading to high Fe : C uptake ratios of heterotrophic bacteria in the upper mesopelagic. The rapid cycling and high demand for iron at 300 m suggest differences in microbial metabolism and iron acquisition in the mesopelagic compared to surface waters. Together, changes in siderophore production and consumption over the seasonal cycle suggest organic carbon availability impacts iron cycling at Station ALOHA.